Application of Derivatization in Fatty Acids and Fatty Acyls Detection: Mass Spectrometry‐Based Targeted Lipidomics. Issue 8 (11th May 2020) - Xiang, Li; Zhu, Lin; Huang, Yu; Cai, Zongwei
Abstract: Mass spectrometry (MS) has become an indispensable technique in the analysis of fatty acids (FAs) and fatty acyls due to its superior sensitivity and selectivity. Chemical derivatization is often introduced in MS‐based analysis because of the inherent poor ionization efficiency and selectivity of FAs and fatty acyls. This critical review presents an overview of commonly used MS platforms including gas chromatography‐MS, liquid chromatography‐MS, and mass spectrometry imaging combined with representative derivatization reagents for FAs and fatty acyls based on different chain‐lengths, saturation degrees, and conjugation groups. The method applications and limitations as well as critical derivatization conditions in different biological matrices are summarized. Special remarks on the chemical derivatization for MS‐based analysis are provided. Future perspectives associated with the detection of FAs and fatty acyls are discussed. This review provides valuable information and suggestions for the targeted detection of interested FAs and fatty acyls using different MS‐based platforms. Abstract : Derivatization in targeted lipidomics analysis of fatty acids and fatty acyls by mass spectrometry is increasingly becoming an indispensable technique. An overview of commonly used mass spectrometry (MS) platforms including gas chromatography‐MS, liquid chromatography‐MS, and mass spectrometry imaging combined with representative derivatization reagents for fatty acids and fatty acyls based on different chain‐lengths, saturation degrees, and conjugation groups is presented.